ENHANCING TEACHING EFFECTIVENESS THROUGH INNOVATIVE PEDAGOGICAL STRATEGIES - O'rinboyeva Madinaxon Salohiddin qizi; Rayimaliyeva Yokutxon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The teaching and learning process involves transferring knowledge from teachers to students, representing a blend of elements where an educator discerns learning objectives, crafts teaching materials, and executes teaching strategies. Simultaneously, learning remains a pivotal consideration for teachers when instructing students. The study examined various scholarly articles, teaching methodologies, and inclusive practices to evaluate teaching efficacy in higher education contexts. The research aims to appraise teaching effectiveness within a higher education framework, utilizing experimental research methods (primarily reflection) coupled with literary analyses to scrutinize theories alongside practical applications derived from university experiences. The findings indicate that offering constructive formative feedback and incorporating role-playing activities significantly boost students' confidence and self-esteem. Furthermore, creating an active learning environment fosters inclusivity and enhances both faculty and student academic achievements. These research outcomes will empower educators to establish and execute inclusive teaching and learning environments, heightening learner expectations and academic performance.